2020
DOI: 10.3390/app10144903
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin Forms and Levels on Vitamin Bioavailability and Growth Performance in Piglets

Abstract: The objective of this study was to quantify the relative bioavailability of microencapsulated vitamins A and E in nursery pigs and compare the effects of vitamin forms and vitamin levels on the plasma vitamin content and growth performance of weaned piglets. In experiment (Exp.) 1, 12 nursery pigs (fitted with jugular catheters) were supplied at 0 h with non-microencapsulated or microencapsulated vitamin A and E. Blood samples were collected at 1, 3, 6, 9, 12, 16, 18, 21, 24, 27, 30, 36, 48, and 72 h after fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…A potential limitation of this study is the interaction between native vitamins and synthesized vitamins. The current study found that the blood distribution of retinol after oral vitamin administration was consistent with previous research [14,19]. Jang et al investigated temporal plasma vitamin status in a 20-day trial period for suckling pigs after high dose of fat-soluble vitamins administration [20].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A potential limitation of this study is the interaction between native vitamins and synthesized vitamins. The current study found that the blood distribution of retinol after oral vitamin administration was consistent with previous research [14,19]. Jang et al investigated temporal plasma vitamin status in a 20-day trial period for suckling pigs after high dose of fat-soluble vitamins administration [20].…”
Section: Discussionsupporting
confidence: 88%
“…Catheters were flushed daily with heparinized sterile saline to prevent blockage. This procedure was described previously [13,14]. At the day before the start of the experiment, pigs fasted overnight except for water so that the experimental meal containing the tested substance could be finished in a short time.…”
Section: Animal Surgery and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is the increasing awareness of the detrimental effects of the excessive minerals to the environment, as well as the soaring cost of vitamins. It has been demonstrated that removing of vitamins and trace minerals in some life stages dose not affect the pig performance response [27][28][29][30]. These are some reasons the lack of performance response resulting from vitamin fortification.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors try to quantify the relative bioavailability of microencapsulated vitamins A and E in nursery pigs and compare the effects of vitamin forms and vitamin levels on the plasma vitamin content and growth performance of weaned piglets. Results show that microencapsulation can improve the bioavailability of vitamins, and supplementation with high levels of vitamins was able to improve the growth performance of the piglets [14].…”
Section: New Trends In Biosciencesmentioning
confidence: 95%